HUBUNGAN KEWENANGAN ANTARA MAHKAMAH AGUNG DAN KOMISI YUDISIAL TERHADAP PENGAWASAN ETIKA HAKIM DALAM PERSPEKTIF HUKUM ISLAM - Ningsih, Wahyu; Rohmadi, Rohmadi; Masril, Masril (Fakultas Syari'ah Institut Agama Islam Negeri (IAIN) Bengkulu, 2019)
Abstract: Oversight carried out by the Supreme Court and Judicial Commission will be very closely related to the independence of judges in deciding a case. The authority of the Supreme Court and the Judicial Commission in terms of ethical oversight of judges is intended to maintain and uphold the honor, dignity, and behavior of judges. From the results of the study found that the relationship between the authority of the Supreme Court and the Judicial Commission on the ethical supervision of judges must not exceed the authority regulated by the Act. The authority of the Supreme Court in following up the judicial ethics oversight report by the Judicial Commission, namely if the Supreme Court considers it appropriate or not, the Supreme Court notifies the Judicial Commission. In Islamic law supervision is carried out structurally operationally by the judicial institution Qadi al-Qudat and spiritually by Allah SWT.Keywords: Oversight; Authority; Supreme Court; Judicial Commission; Judge.